Computed tomography morphometric comparison of the pelvis in children with and without rectal prolapse in Niger - SALIFOU, Seyni Taoueye; Innoussa, Daouda Bako; Lalèyè, C.M.; HADONOU, Ayaovi Armel (My University, 2023)
Background: Rectal prolapse is a public health problem that affects all sexes at different ages. It is one of the most frequent reasons for consultation in pediatric surgery. The main causes are chronic constipation and diarrhea or both. The increase in abdominal pressure, whatever its cause, is an essential factor favoring the occurrence of rectal prolapse. The anatomical factors related to the morphology of the pelvis and sacrum are unknown. The objective of this work was to compare the morphometric variations of the pelvis in children aged from 0 to 15 years with and without rectal prolapse. Methods: This was a case-control study of 128 children (64 males) living in Niger, children without rectal pro- lapse (controls) were paired to those with rectal prolapse by age for both sexes. Morphometric parameters were measured on computed tomography scans. The length, concavity and slope of the sacrum were measured. Antero-posterior, bi-ischiatic, and sub-sacro-sub-pubic diameters were measured on the pelvis. Results: In girls and boys with rectal prolapse, with the generalized linear model the sacral length was signifi- cantly increased with p = 0.0005 and sacral concavity decreased as compared with controls with p = 0.0007. The sacral slope has probably also an effect but impaired by large variations. There were no significant changes in other pelvic parameters. Conclusion: The morphology of the sacrum is an anatomical factor probably related to the occurrence of rectal prolapse in children.
Keywords: Rectal prolapse; Bone pelvis; Sacrum; Computed tomography